Implementasi Multimodal Emotion Recognition Menggunakan CNN-BiLSTM-Attention pada Audio dan Mobilenetv2 pada Ekspresi Wajah - Ai Solihah; Alun Sujjada; Ivana Lucia Kharisma (TIN: Terapan Informatika Nusantara, 2026)
The advancement of artificial intelligence technology has significantly contributed to the development of emotion recognition systems capable of understanding human emotional states more accurately. However, unimodal approaches that rely on a single data source, such as speech or facial expressions, still face limitations when dealing with dynamic environmental conditions. This study aims to implement a Multimodal Emotion Recognition system by integrating audio and visual modalities to improve emotion detection accuracy. The audio modality is processed using a CNN-BiLSTM-Attention architecture with Mel-Spectrogram representations as input, while the visual modality is analyzed using MobileNetV2 to recognize facial expressions. The integration of both modalities is performed using the Late Fusion method at the decision level through a weighted fusion approach, assigning weights of 0.4 and 0.6 to the audio and visual modalities, respectively. This research employs an experimental method with a quantitative approach. The research stages include literature review, data collection, audio and video preprocessing, model design, model training, multimodal integration, and system evaluation. Audio data are transformed into Mel-Spectrogram features, while video data are processed using MediaPipe Face Detection to extract facial regions prior to emotion classification. The proposed system is designed to recognize three emotional classes: neutral, happy, and angry. Model performance is evaluated using a Confusion Matrix, accuracy, precision, recall, and F1-score metrics. The results indicate that multimodal integration using the Late Fusion method effectively leverages the strengths of each modality, resulting in more accurate and robust emotion detection compared to unimodal approaches. Furthermore, the developed system is capable of performing real-time emotion classification through a camera and microphone, making it potentially applicable in various domains, including education, customer service, human-computer interaction systems, and user emotional state monitoring. The primary contribution of this research is the development of a multimodal emotion recognition system that integrates a CNN-BiLSTM-Attention model for the audio modality and MobileNetV2 for the visual modality using a late fusion method. The proposed system leverages emotional information from both modalities simultaneously to enhance the accuracy and stability of real-time emotion detection, thereby offering an alternative solution for the development of AI-based human-computer interaction systems.